Focused Information Criterion for Series Estimation in Partially Linear Models. (9th February 2017) - Sueishi, Naoya; Yoshimura, Arihiro
Abstract : This paper proposes a focused information criterion for variable selection in partially linear models. Our criterion is designed to select an optimal model for estimating a focus parameter, which is a parameter of interest. We estimate the model using the series method and jointly select the variables in the linear part and the series length in the nonparametric part. A Monte Carlo simulation shows that the proposed focused information criterion successfully selects the model that has a relatively small mean squared error of the estimator for the focus parameter.